2012
DOI: 10.1292/jvms.11-0380
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between NF-κB Expression and Malignancy of Canine Mammary Gland Tumor Tissues

Abstract: AbSTRACT. In this study, the nuclear expression of nuclear factor kappa B (NF-κB) in 48 tissues specimens from 25 canine spontaneous mammary gland tumor (MGT) patients was assessed by immunohistochemistry to compare their levels with clinical features, histological types, prognostic outcomes and proliferative activities, including the mitotic index (MI) and cylcinD1 expression. Twelve of eighteen (66.7%) malignant tumor tissues showed greater than 10% nuclear staining, while benign tumor and hyperplastic tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Non‐specific binding was blocked by incubation of slides for 10 minutes with a protein‐blocking agent (Dako Products, Carpinteria, CA) before application of the primary antibody. Slides were then incubated overnight in a moist‐chamber with the following primary antibodies: canine cross‐reactive monoclonal antibody against NF‐κB (p65) (BD Transduction Laboratories, Lexington, KY)55 diluted 1 : 50, and a goat polyclonal to CD11b + (anti‐CD11b + antibody ‐ ref. N° ab62817) (ABCAM, San Francisco, CA) diluted 1 : 50.…”
Section: Methodsmentioning
confidence: 99%
“…Non‐specific binding was blocked by incubation of slides for 10 minutes with a protein‐blocking agent (Dako Products, Carpinteria, CA) before application of the primary antibody. Slides were then incubated overnight in a moist‐chamber with the following primary antibodies: canine cross‐reactive monoclonal antibody against NF‐κB (p65) (BD Transduction Laboratories, Lexington, KY)55 diluted 1 : 50, and a goat polyclonal to CD11b + (anti‐CD11b + antibody ‐ ref. N° ab62817) (ABCAM, San Francisco, CA) diluted 1 : 50.…”
Section: Methodsmentioning
confidence: 99%
“…A study evaluating immunohistochemical labeling of NF-kB p65 in canine mammary tumors found that higher nuclear expression of NF-kB was correlated with larger tumor size, lymph node metastasis, and higher mitotic index, while there was no correlation with distant metastasis or cyclin D1 expression. 59 Another study identified an association between increased NF-kB activation and decreased surivival in dogs with mammary cancer. 54…”
Section: Mammary Cancermentioning
confidence: 99%
“…CHIP is known to be involved in ubiquitination and degradation of certain oncoproteins, such as NF-κB, SRC-3 and mutant p53 [ 17 , 18 , 25 , 32 ]. Previous research has shown that NF-κB is a useful prognostic factor for canine mammary gland tumor [ 24 ]. It regulates downstream genes, including IL-6 , IL-8 , MMP-2 , VEGF and cyclooxygenase-2 , to promote proliferation, survival, angiogenesis and metastasis of tumors [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%